Efficacy of selected pesticides against synanthropic mites under laboratory assay - Stará, Jitka; Stejskal, Václav; Nesvorná, Marta; Plachý, Jan; Hubert, Jan (Pest management science, 2011)
BACKGROUND: The efficacies of organophosphate pesticides, single-compound versus multicompound pyrethroid formulations and relatively novel unclassified insecticides/acaricides were compared to find the lowest dosage and highest efficacy for the control of Dermatophagoides farina (Hughes), D. pteronyssinus (Trouessart) and Tyrophagus putrescentiae (Schrank). Formulated active ingredients (AIs) were diluted in water and applied onto filter paper in experimental chambers with ten unsexed adult mites in six replicates. Mite mortality was checked after 24 h. The security index (SI) was calculated for all of the AIs by dividing the recommended rate by the LD(90) determined for each species. RESULTS: The tested organophosphates had high LD(90) and low SI values. The single-compound pyrethroids were ineffective (deltamethrin and beta-cyfluthrin) or had high LD(90) and low SI values (cyphenothrin, permethrin, pyrethrum and bifenthrin). The multicompound miticides had low LD(90) and high SI values which increased from deltamethrin/S-bioallethrin to permethrin/S-bioallethrin/piperonyl butoxide to permethrin/pyriproxyfen/benzyl benzoate. Abamectin, pyridaben, propargite and flufenoxuron were highly active against Dermatophagoides spp. Neem (Acarosan duo) was highly active against all mite species tested. CONCLUSION: The available formulations of multicompound pyrethroids (permethrin/S-bioallethrin/piperonyl butoxide, permethrin/pyriproxyfen/benzyl benzoate), benzyl benzoate, neem and some field acaricides are effective in suppression of synanthropic mites in laboratory assays. Their LD(90) are lower than those of traditionally used organophosphates or single-compound pyrethroid formulations.
Keywords: biotest; Acaricides; Pest Control; Animals; Organophosphorus Compounds; kontrola škůdců; preklinické hodnocení léčiv; zvířata; akaricidy; Drug Evaluation, Preclinical; roztoči; organofosforové sloučeniny; Biological Assay; Mites